Improved MAP Based Algorithm for Image Super-resolution Restoration - Jiwen Cui; Kunpeng Feng; Wenlong Yu (2013 Seventh International Conference on Image and Graphics, 2013)
To enhance high frequency details of image super-resolution restoration, an algorithm based on improved MAP estimation is proposed. In this paper, POCS and MAP are combined in a special way. POCS is used in the MAP estimation so that advantages of the both algorithms can be taken. Experiment shows it is effective by comparing with the results of typical MAP method.